If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 6) = -4(x + 21) Reorder the terms: 2(6 + x) = -4(x + 21) (6 * 2 + x * 2) = -4(x + 21) (12 + 2x) = -4(x + 21) Reorder the terms: 12 + 2x = -4(21 + x) 12 + 2x = (21 * -4 + x * -4) 12 + 2x = (-84 + -4x) Solving 12 + 2x = -84 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 12 + 2x + 4x = -84 + -4x + 4x Combine like terms: 2x + 4x = 6x 12 + 6x = -84 + -4x + 4x Combine like terms: -4x + 4x = 0 12 + 6x = -84 + 0 12 + 6x = -84 Add '-12' to each side of the equation. 12 + -12 + 6x = -84 + -12 Combine like terms: 12 + -12 = 0 0 + 6x = -84 + -12 6x = -84 + -12 Combine like terms: -84 + -12 = -96 6x = -96 Divide each side by '6'. x = -16 Simplifying x = -16
| 2xy=40 | | -2(x+5)=-7x+25 | | 2(x-4)=4(x-7) | | 35+7(x+20)=3x+47 | | 2x*4y=32 | | 3x+31=5(x+10)+25 | | ((91*0.05)+(96*0.05)+(100*0.1)+(95*0.15)+(91*0.15)+(x*0.5))=95 | | -2(x-12)=-8x-30 | | -3x+6=-6x-24 | | 2x*4y=16 | | -2(x+12)=-8x+30 | | -2x-9=-5x+24 | | 1=10-3v | | -2x+9=-5x+24 | | 6x*2=48 | | 16-2g=10 | | (x+(2+i))(x-(2-i))=0 | | 18 = h3+ 15 | | 3x+2y=y-4+5x-y | | 5x^2+y^2=1 | | 32x-12=-18 | | X+3=5+4 | | ln(3x+1)=-4 | | 27000*x-0,5=10000*x | | 14(X)+48(1-X)=47.5 | | 78(X)+47(1-X)=47.7 | | 16y-20=60-4y | | 0.4x+16.5=x-1.62 | | X=Z-(X*Y) | | x=(x-1)(1.075) | | 9x+2y=192 | | 2x^2+4x+21=0 |